(untitled) (Archaeologia Adriatica, 2011)
Luke is one of the largest and richest classical Antiquity sites on the island of Brač. there have been no archaeological excavations, but several field surveys have been conducted at the site. The site has been known since 1899, when an altar stone dedicated to Jupiter Dolichenus was unearthed. the article describes the artefacts found in the spring of 2003. The artefacts were dated to the period from the first to the fifth century.